Machining of biocompatible materials: a review - Saptaji, Kushendarsyah; Mebrahitom, A.; Azmir, Azhari (Springer-Verlag, 2018)
The need for more effective and efficient manufacturing processes to transform the biocompatible materials into high standard artificial human body components (implants) is rapidly growing. Machining of biocompatible materials as one of the key processes in manufacturing of implants need to be improved due to the significant effects of machined surface quality to the compatibility and osseointegration with human organs such as tissues, bones, and environment of the human body. The challenges of machining biocompatible materials due to their applications as bio-implants in the human body and the nature of materials properties and microstructures have been explored and solved by various researchers. This article reviews the trends and developments of the machining of biocompatible materials. A range of possible machining technologies and strategies on various biocompatible materials using conventional (milling, turning and drilling) and non-conventional or advanced (abrasive water jet machining (AWJM), ultrasonicmachining (USM), ion beam machining (IBM), laser beam machining (LBM), electrical discharge machining (EDM), and electron beam machining (EBM)) are presented and discussed. This review also examines the emerging new technologies such as additives manufacturing and hybrid processes as potential solutions and future research trends in order to fulfill the high standard requirements for a wider range of applications of the biomaterials.